Infrastructures of Feeling and the Right to the City. (December 2019) - Rosati, Clayton
For over sixteen years, I have been tracing and retracing an idea through a set of projects involving the political economy and cultural politics of infrastructure—especially, the infrastructure of media. When I began those projects as a graduate student, my concern was a frustration with the image-centered studies of media and culture, which tended to get bogged down in representational politics and a focus on the micropolitics of interpretation and use. Infrastructure attracts similar debates, as anything from a train tunnel to a water use meter can be appropriated and used in unauthorized or subversive ways. The physicality of infrastructure and the relationships it has with the materiality of ideas, ideologies, and social processes is a growing dimension of cultural inquiry around inequality and power, especially in the study of electronic devices. In this article, I will report on a strand of my research that explores an urban history of interactive media that unfolds into our contemporary world of automated ecologies of surveillance, marketing, disinformation, and covert politics. In recent iterations, this strand intersects with the increasingly popular concept of the 'right to the city.'